2018
DOI: 10.1155/2018/6794508
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Acclimation to Chronic Hypoxia Leads to Submandibular Gland and Periodontal Alterations: An Insight on the Role of Inflammatory Mediators

Abstract: The exposition to hypoxia is a stressful stimulus, and the organism develops acclimation mechanisms to ensure homeostasis, but if this fails, it leads to the development of pathological processes. Considering the large number of people under hypoxic conditions, it is of utmost importance to study the mechanisms implicated in hypoxic acclimation in oral tissues and the possible alteration of some important inflammatory markers that regulate salivary and periodontal function. It is the aim of the present study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In order to understand how the IL-6/JAK2/STAT3/ MMP-9 pathway regulates the microvessels under hypoxia, the specific processes should be analyzed in detail. IL-6, one of the dominant inflammatory cytokines [24][25][26][27], markedly upregulates the phosphorylation of JAK2 by binding to IL-6 receptor α (IL-6Rα) and activating gp130 [12]. P-JAK2 subsequently induces STAT3 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand how the IL-6/JAK2/STAT3/ MMP-9 pathway regulates the microvessels under hypoxia, the specific processes should be analyzed in detail. IL-6, one of the dominant inflammatory cytokines [24][25][26][27], markedly upregulates the phosphorylation of JAK2 by binding to IL-6 receptor α (IL-6Rα) and activating gp130 [12]. P-JAK2 subsequently induces STAT3 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have validated this and have identified the pathways regulating the process [18][19][20][21][22][23]. Proinflammatory cytokine interleukin-6 (IL-6) released from inflammatory cells binds to IL-6 receptor α and active gp130 to induce the phosphorylation of JAK2 (P-JAK2), in response to hypoxia [24][25][26][27]. P-JAK2 promotes the overexpression of MMP-9 in the vascular endothelial cells, leading to angiogenesis and BM degradation by activating the phosphorylation of STAT3 tyrosine residues (P-STAT3) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Protocols were approved by the institutional Animal Care and Use Committee (IACUC, N o 11/06/2012-23) of the School of Dentistry, University of Buenos Aires. Rats were randomly assigned to one of three groups of ten animals each subject to the following conditions: Control group (C): normoxia; Chronic Intermittent Hypoxia (CIH): exposure to discontinuous hypoxia (600 mbar, equivalent to 4,000 meters of simulated altitude) in a simulated high altitude chamber for 18 h/d, five days a week for 30 days (time of exposure to hypoxia was approximately 50 % of the experimental period); Chronic Continuous Hypoxia (CCH): continuous exposure to the same ambient pressure in the simulated high altitude chamber as the CIH group but for 23.5 h/d seven days a week for 30 days (time of exposure to hypoxia was almost 100 % of the experimental period) [17]. Environmental oxygen pressure was 12.6 kPa during the hypoxic period in both hypoxic protocols.…”
Section: Experimental Designmentioning
confidence: 99%
“…Chronic exposure to hypoxia induced the expression of high levels of inflammatory mediators such as prostaglandin E2, decreased immunoreactivity of hypoxia-inducible factor 1α, and the presence of apoptotic nuclei and irregular secretion granules in oral tissue, indicating the damaging role of these inflammatory mediators during hypoxia. 36 Another study used a rat periodontitis model in a simulated high-altitude hypoxic environment to measure the association of cytokines and clinical periodontal parameters under hypoxic conditions and compare the findings with those obtained in normal conditions. The results showed an increase in tumor necrosis factor α and prostaglandin E2, and a decrease in interleukin-8 levels in the gingival crevicular fluid of the hypoxia group in relation to increased attachment loss, pocket depth, plaque index, and bleeding index.…”
Section: Periodontal Inflammation and Inflammatory Mediatorsmentioning
confidence: 99%
“…Many studies have recorded the health problems related to living in or travelling to high altitudes, and have discussed the oral features of living at high altitudes, 13,14 including periodontal inflammation, 15,16 saliva production, 17 dental pain and anesthesia, 18 inflammatory mediators and bleeding index, 19 and dental fluorosis. 20 However, studies covering the effect of high altitudes on the oral cavity are relatively fewer, and many of them lack conclusive findings or require more detailed investigation.…”
Section: Introductionmentioning
confidence: 99%